Extra-thick hot-rolled H-section steel and its production method
The controlled chemical composition and cooling processes in the production of hot-rolled H-section steel with flange thicknesses of 90 mm to 150 mm address mechanical property inconsistencies, achieving enhanced yield and tensile strengths, elongation, and impact resistance, suitable for heavy structural applications.
Patent Information
- Application Number
- JP2023540157
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-04
- Filing Date
- 2021-10-27
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-10-27
AI Technical Summary
Existing methods for producing hot-rolled H-section steel with flange thicknesses of 90 mm to 150 mm fail to ensure consistent mechanical properties in the thickness direction, particularly yield strength, tensile strength, elongation, and impact resistance, due to inadequate control of microstructure and cooling processes, leading to increased alloy costs and production challenges.
A hot-rolled H-beam steel with specific chemical compositions (C, Si, Mn, Cr, Cu, Nb, V, Ti, Al, N, P, S, O) and controlled cooling processes, including high-speed cooling before and after rolling, to achieve a microstructure dominated by acicular ferrite with controlled bainite and residual austenite, ensuring uniform mechanical properties across the thickness.
The method produces H-section steel with flange thicknesses of 90 mm to 150 mm, achieving yield strengths of 460 MPa or more, tensile strengths of 540 MPa or more, elongations of 24.0% or more, and impact energies of 80J or more at -20°C, meeting the Z35 level, suitable for heavy structural applications with improved production feasibility and reduced costs.
Smart Images

Figure 0007600409000005 
Figure 0007600409000006 
Figure 0007600409000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of metal material production, specifically to hot-rolled H-beam of extra-thickness and its production method. [Background technology]
[0002] With the rapid development of the economy and society, emphasis is being placed on safety, comfort and aesthetics in the construction of high-rise buildings, large venues, bridge main towers and the like. Heavy steel structures are being adopted in the design, with hot-rolled H-beams with extra-thick flange thicknesses of 90mm to 150mm being the core supporting members.
[0003] After a long period of practice, it has become clear that the overall mechanical properties of the flange of hot-rolled H-shaped steel are weaker than those of the web plate. Standard GB / T2975 also stipulates that sampling should be done from the flange to evaluate the mechanical properties, and it is common in the industry to take the flange of hot-rolled H-shaped steel as the subject of description. It is recognized in the industry that a thick blank can be rolled to a thin-walled standard to obtain excellent mechanical properties under high pressure. However, in order to roll hot-rolled H-shaped steel with an extremely thick flange thickness of 90mm to 150mm using this method, an extremely thick and extremely large blank far exceeds the existing dimensions, and investment must be made in the construction of new continuous casting equipment and steel rolling equipment, which is very costly, and the quality control of the inside and surface of the blank is very difficult and difficult to achieve. From the perspective of feasibility and economy, if a beam blank is used for rolling, the rolling reduction rate in the thickness direction of the flange from the blank to the finished product is 13% to 30%, which is acceptable.
[0004] In patent document CN103987866B, a beam blank of Ni-Cu-BV-Ti component system is used, and through the heating-rough rolling-finish rolling process, the finishing rolling interpass cooling or the rolling after high speed cooling is used to form a room temperature structure of bainite + ferrite / martensite, and a hot rolled H-shaped steel with a flange thickness of 100mm ~ 150mm is produced, and the yield strength level is 450MPa or more. In patent document CN109715842A, a beam blank of Nb-V-Ti component system (Cr, Mo, Ni, Cu elements can be added) is used, and through the heating-rough rolling-finish rolling process, the finishing rolling interpass cooling or the rolling after high speed cooling is used to form a room temperature structure of ferrite + martensite / austenite, and a hot rolled H-shaped steel with a flange thickness of 40mm ~ 140mm is produced, and the yield strength level is 450MPa or more. In the above two methods, the bainite content at the 1 / 4 position of the flange thickness is 60% or more, and the ferrite content is 60% or more (grain size 35μm or less), but the structure and content in the entire thickness direction of the flange are not controlled. When these methods are applied to the production of products with flange thicknesses of 90mm or more, the performance in the thickness direction cannot be guaranteed.
[0005] In patent documents CN105586534B, CN103938079B, CN110484822A, and CN108893675A, beam blanks of V, V-Ti, Ni-V-Ti, and Ni-Nb-V-Mo composition systems are used, respectively, and a room temperature structure of ferrite + pearlite / bainite is formed through heating-blooming-rough rolling-air cooling / water cooling processes, producing hot-rolled H-section steel with a flange thickness of 45 mm or less, with a yield strength level of 355 MPa to 500 MPa, and meeting the low temperature toughness requirement of -20 ℃ to -40 ℃. The above four methods do not control the cooling and structure of the core. When applied to the production of products with flange thicknesses of 90 mm or more, the initial cooling temperature of the core is high and the cooling rate of the entire cross section by air cooling is low, so large-sized blocky ferrite is likely to precipitate, exhibiting a chain-like or network-like distribution, and the precipitated phase is also likely to aggregate and become coarse. As a result, the strength, plasticity, toughness and through-thickness performance of the product cannot be guaranteed, and the addition of elements such as Ni and Mo increases the alloying cost.
[0006] In the patent document CN105586534B, a Ni-V-Ti component beam blank is used, and a room temperature structure of ferrite + pearlite is formed through the processes of heating-blooming-rough rolling-air cooling to produce a hot-rolled H-section steel with a flange thickness of 36 mm or less, with a yield strength level of 355 MPa and excellent low temperature resistance. This method specifies that the rolling reduction rate in each pass of the rough rolling stage should be 20% or more, but this cannot be achieved when rolling a product with a flange thickness of 90 mm or more from the beam blank, and no measures are taken to enhance deformation penetration and cooling penetration, so the strength, plasticity, toughness and thickness direction performance of the product cannot be guaranteed.
[0007] In patent documents CN107964626B and CN107747043B, the former uses a beam blank of Nb-B composition system, and forms a room temperature structure of tempered sorbite + ferrite + diffusely distributed carbide through the processes of heating-rough rolling-finish rolling-quenching-tempering, while the latter uses a beam blank of V-Ti-Ni-Mo-Cu-Cr-Al composition system, and forms a tempered martensite structure through the processes of heating-rough rolling-finish rolling-quenching-offline tempering, so that hot-rolled H-section steel with a yield strength level of 500MPa to 650MPa can be produced. The above two methods are intended for products with thin flange thickness and require high-speed cooling conditions to be achieved throughout the entire thickness. When these methods are applied to the production of products with flange thicknesses of 90 mm or more, the quenching critical cooling rate cannot be achieved throughout the entire thickness, the initial structure required for online or offline heat treatment cannot be obtained, the starting cooling temperature of the core is high and the cooling rate is low, and sorbite / martensite + diffusely distributed carbides cannot be formed, so the strength, plasticity, toughness and thickness direction performance of the product cannot be guaranteed, and the addition of Ni and Mo elements increases the alloying cost.
[0008] For the above reasons, there is an urgent need for extra-thickness hot-rolled H-section steel and a method for producing the same in order to solve these problems. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide extra-thickness hot-rolled H-section steel and a production method thereof in order to solve the problem of improving the mechanical properties, particularly the performance in the thickness direction, of hot-rolled H-section steel with a flange thickness of 90 mm to 150 mm. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention adopts the following technical solutions.
[0011] This is a hot-rolled H-section steel of extra-thickness standard, and its chemical composition, in mass percentage, is as follows: C: 0.04~0.11, Si: 0.10~0.40, Mn: 0.40~1.00, Cr: 0.40~1.00, Cu: 0.10~0.40, Nb: 0.020~0.060, V: 0.040~0.100, Ti: 0.010~0.025, Al: 0.010~0.030, N: 0.0060~0. The chemical composition is 0.30%≦CEV≦0.48%, calculated according to CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15.
[0012] Alternatively, the chemical composition of the H-shaped steel is, in mass percentage, C: 0.04~0.07, Si: 0.10~0.30, Mn: 0.80~1.00, Cr: 0.40~0.90, Cu: 0.10~0.25, Nb: 0.040~0.060, V: 0.040~0.080, Ti: 0.010~0.015, Al: 0.010~0.020, N: 0.0060~0.0100. , P:≦0.015, S:≦0.005, O:≦0.0060, and the following conditions are met: 0.090%≦Nb+V+Ti≦0.130%, 6.5≦(V+Ti) / N≦8.5, with the balance being Fe and trace amounts of residual elements. The calculation is based on CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15, and the chemical composition satisfies 0.30%≦CEV≦0.43%.
[0013] Optionally, the chemical composition of the H-beam, by mass percentage, contains C: 0.07 - 0.11, Si: 0.30 - 0.40, Mn: 0.40 - 0.80, Cr: 0.90 - 1.00, Cu: 0.25 - 0.40, Nb: 0.020 - 0.040, V: 0.080 - 0.100, Ti: 0.015 - 0.025, Al: 0.020 - 0.030, N: 0.0100 - 0.0120, P: ≤ 0.015, S: ≤ 0.005, O: ≤ 0.0040, satisfies 0.130% < Nb + V + Ti ≤ 0.170%, 8.5 ≤ (V + Ti) / N ≤ 10.5, the balance being Fe and trace residual elements, and the calculation is performed according to CEV = C + Mn / 6 + (Cr + Mo + V) / 5 + (Ni + Cu) / 15, and the chemical composition satisfies 0.40% ≤ CEV ≤ 0.48%.
[0014] Preferably, at a position 1 / 6 of the width and 1 / 4 of the thickness from the end in the flange of the H-beam, the microstructure, by area percentage, contains 85% - 98% acicular ferrite, and the remaining structure is bainite or retained austenite, the content of bainite is 2% or less, the width dimension of the ferrite grain is 40 μm or less, and the difference in the content of acicular ferrite in different regions along the thickness direction of the flange is 16% or less.
[0015] Optionally, at a position 1 / 6 of the width and 1 / 4 of the thickness from the end in the flange of the H-beam, the microstructure, by area percentage, contains 85% - 91% acicular ferrite, and the remaining structure is bainite or retained austenite, the content of bainite is 2% or less, the width dimension of the ferrite grain is 20 μm or less, and the difference in the content of acicular ferrite in different regions along the thickness direction of the flange is 9% or less.
[0016] Optionally, at a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange of the H-shaped steel, the microstructure contains, in area percentage, 91% to 98% acicular ferrite, the remaining structure being bainite or retained austenite, the bainite content being 1% or less, the width dimension of the ferrite crystal grains being 20 μm to 40 μm, and the difference in the acicular ferrite content in different regions along the thickness direction of the flange being 9% to 16%.
[0017] Preferably, at a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange of the H-shaped steel, the tensile yield strength at room temperature is 460 MPa or more, the tensile strength is 540 MPa or more, the breaking elongation is 24.0% or more, the impact energy value at -20°C is 80 J or more, and the performance in the thickness direction reaches the Z35 level.
[0018] Preferably, the thickness of the flange of the H-section steel is 90 mm to 150 mm.
[0019] The present invention provides another technical solution, which is a method for producing hot rolled H-beam of extra thick gauge as set forth in any one of claims 1 to 8, which includes the steps of heating a blank under conditions of a heating temperature of 1200°C to 1350°C and a heating time of 120 min to 180 min, performing blooming so that after the rolling is completed, the surface temperature of the flange is 1000°C or higher, and performing fountain cooling at a cooling rate of 20°C / s or more so as to rapidly cool the flange surface to 700°C to 800°C, and then putting the blank into a universal mill for rolling, and after the rolling by the universal mill is completed, firstly, by fountain cooling, the flange surface of the rolled material is rapidly cooled to 480°C to 530°C at a cooling rate of 5°C / s to 13°C / s, and then performing air cooling.
[0020] Preferably, the beam blank is subjected to blooming, and after the rolling is completed, the surface temperature of the flange is 1020° C. or more. Effect of the Invention
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] 1. The hot-rolled H-section steel of this extra-thick standard has a flange thickness of 90mm to 150mm, and has excellent comprehensive mechanical properties, such as a yield strength of 460MPa or more, a tensile strength of 540MPa or more, a breaking elongation of 24.0% or more, and an impact energy of 80J or more at -20℃. In particular, the performance in the thickness direction can reach the minimum Z35 level, and can well meet the requirements for heavy-duty supporting structural members of high-rise buildings, large plazas, bridge structures, etc.
[0023] 2. In the production method of the hot-rolled H-beam of the extra-thick specification, when the flange is cooled quickly before rolling by the universal mill, a certain temperature gradient can be formed from the surface to the core in the thickness direction of the flange. In the rolling process, the surface temperature is low and the deformation resistance is large, and the compression deformation continues to progress with rolling, and the deformation gradually penetrates into the core, which has a higher temperature and a smaller deformation resistance. With the increase in the temperature gradient, the deformation penetration effect is enhanced, the strain accumulation in the core increases, and the difference in strain accumulation from the surface to the core decreases accordingly. By increasing the strain accumulation, the nucleation position increases, the driving force increases, and the precipitation of acicular ferrite is promoted and refined. Reducing the difference in strain accumulation in the thickness direction of the flange is helpful to reduce the difference in the content of the structure in different regions in the thickness direction and improve the uniformity of the structure.
[0024] 3. The production method of the extra-thickness hot-rolled H-section steel uses chemical composition control, rapid cooling before rolling by a universal mill, and stepwise cooling after rolling to form a room temperature structure mainly composed of acicular ferrite with the remainder being bainite or retained austenite, and limits the content of acicular ferrite, the grain size and the content of bainite to reduce the variation in structure along the thickness direction of the flange, and uses the combined effects of structure, precipitation, solid solution and microcrystalline strengthening to obtain an extra-thickness hot-rolled H-section steel with excellent comprehensive mechanical properties, which has a relatively low production cost, high feasibility for production, and is suitable for mass production. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a typical microstructure diagram of an H-section steel according to the present invention at room temperature. [Diagram 2] This is a schematic diagram of the structure of a typical H-shaped steel, and the diagram shows a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The chemical composition of the extra thick hot rolled H-section steel according to the present invention is, in mass percentage, C: 0.04-0.11, Si: 0.10-0.40, Mn: 0.40-1.00, Cr: 0.40-1.00, Cu: 0.10-0.40, Nb: 0.020-0.060, V: 0.040-0.100, Ti: 0.010-0.025, Al: 0.010-0.030, N: 0.0060. ~0.0120, P:≦0.015, S:≦0.005, O:≦0.0060, and the following are satisfied: 0.090%≦Nb+V+Ti≦0.170% and 6.5≦(V+Ti) / N≦10.5, with the balance being Fe and trace amounts of residual elements. The calculation is performed according to CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15, and the chemical composition satisfies 0.30%≦CEV≦0.48%.
[0027] More selectively, the chemical components are, in mass percentage, C: 0.04-0.07, Si: 0.10-0.30, Mn: 0.80-1.00, Cr: 0.40-0.90, Cu: 0.10-0.25, Nb: 0.040-0.060, V: 0.040-0.080, Ti: 0.010-0.015, Al: 0.010-0.020, N: 0.0060-0.0100, The chemical composition is 0.30%≦CEV≦0.43%, calculated according to CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15.
[0028] Optionally, the chemical components, by mass percentage, are: C: 0.07 - 0.11, Si: 0.30 - 0.40, Mn: 0.40 - 0.80, Cr: 0.90 - 1.00, Cu: 0.25 - 0.40, Nb: 0.020 - 0.040, V: 0.080 - 0.100, Ti: 0.015 - 0.025, Al: 0.020 - 0.030, N: 0.0100 - 0.0120, P: ≤ 0.015, S: ≤ 0.005, O: ≤ 0.0040, 0.130% < Nb + V + Ti ≤ 0.170%, 8.5 ≤ (V + Ti) / N ≤ 10.5, with the balance being Fe and trace residual elements. The calculation is performed according to CEV = C + Mn / 6 + (Cr + Mo + V) / 5 + (Ni + Cu) / 15, and the chemical components satisfy 0.40% ≤ CEV ≤ 0.48%.
[0029] Specifically, the functions of each element and the compounding ratios of the components (by mass percentage) are based on the following.
[0030] Carbon (C): It increases strength. To obtain this effect, the lower limit is set to 0.04%. When the content exceeds 0.11%, when acicular ferrite is formed, carbides precipitate in a chain or strip shape, breaking the continuity of the matrix, damaging plasticity, toughness, and properties in the thickness direction. Also, since the components are adjacent to the peritectic region, the ends and inner rounded corners of the beam blank are prone to cracking, which has an adverse effect on weldability. Therefore, the upper limit is set to 0.11%.
[0031] Silicon (Si): It is a steelmaking deoxidizing element, which increases strength and improves the fluidity of molten steel during continuous casting. To obtain this effect, the lower limit is set to 0.10%. When the content exceeds 0.40%, the effect of increasing strength is sufficient, and the formation of a mixed structure of martensite and austenite is also promoted, damaging plasticity and toughness. Therefore, the upper limit is set to 0.40%.
[0032] Manganese (Mn): Improves hardenability, improves the stability of austenite at excessively low temperatures through a synergistic effect with Cr, promotes the precipitation of acicular ferrite, improves performance in the thickness direction to a certain extent, and can also increase strength, and in order to obtain this effect, the lower limit is set to 0.40%. If the content exceeds 1.00%, macro components are likely to segregate, pearlite, bainite, or residual austenite is distributed in stripes, the continuity of the matrix is destroyed, and the performance in the thickness direction is impaired, so the upper limit is set to 1.00%.
[0033] Chromium (Cr): Improves hardenability, improves the stability of austenite at excessively low temperatures through a synergistic effect with Mn, promotes the precipitation of acicular ferrite, improves the performance in the thickness direction to a certain extent, and can also increase strength, so the lower limit is set at 0.40%. If the content exceeds 1.00%, the effect of improving hardenability is insufficient, and the precipitation of bainite is also promoted, which impairs plasticity and toughness and has a negative effect on weldability, so the upper limit is set at 1.00%.
[0034] Copper (Cu): It increases strength, and in order to obtain this effect, the lower limit is set to 0.10%. If the content exceeds 0.40%, liquid separation defects will occur on the blank surface, so the upper limit is set to 0.40%.
[0035] Niobium (Nb): precipitates during rolling, inhibits the growth of austenite grains, increases the critical temperature of the austenite non-recrystallized region, increases strain accumulation, helps refine acicular ferrite, increases the work hardening degree of the surface and superficial region, strengthens deformation penetration, and can also improve plasticity, toughness and thickness direction performance, so the lower limit is set to 0.020%. If the content exceeds 0.060%, the effect of increasing the austenite non-recrystallized critical temperature becomes insufficient, the precipitates are coagulated and coarsened, and the pinning effect is reduced, so the upper limit is set to 0.060%.
[0036] Vanadium (V): After rolling, it diffuses and precipitates to increase strength, and in order to obtain this effect, the lower limit is set to 0.040%. If the content exceeds 0.100%, the precipitates become seriously coarsened, and the boundary between the large particles and the matrix is easily cracked, which impairs plasticity and toughness and adversely affects weldability, so the upper limit is set to 0.100%.
[0037] Titanium (Ti): Precipitates during heating and rolling to suppress excessive growth of austenite grains, and in order to obtain this effect, the lower limit is set to 0.010%. If the content exceeds 0.025%, the precipitates will aggregate and coarsen the steel, reducing the pinning effect, and forming brittle fracture bases to further impair toughness, so the upper limit is set to 0.025%.
[0038] Aluminum (Al): A steelmaking deoxidizing element that precipitates during rolling and suppresses the excessive growth of austenite grains, and in order to obtain this effect, the lower limit is set to 0.010%. If the content exceeds 0.030%, brittle inclusions are likely to form, impairing the plasticity, toughness, and thickness direction properties, and nodule formation that causes leakage of molten steel during continuous casting is also likely to occur, so the upper limit is set to 0.030%.
[0039] Nitrogen (N): The precipitation of Ti, V, and Nb requires a synergistic effect with N element, and has a significant effect on the number and distribution of Ti and V precipitates. The precipitation ratio increases significantly with increasing N content, so in order to obtain this effect, the lower limit is set to 0.0060%. If the content exceeds 0.0120%, the precipitation promotion effect becomes sufficient, and the formation of island martensite is also promoted, impairing plasticity and toughness, so the upper limit is set to 0.0120%.
[0040] In order to fully exert the beneficial effects of the precipitation of Nb, V, and Ti elements, the lower limit of Nb+V+Ti is set to 0.090%. If the total content of the three elements is higher than 0.170%, the coarsening of precipitated particles becomes serious, and toughness and plasticity are impaired, so the upper limit of Nb+V+Ti is set to 0.170%. Since the precipitation of Ti and V requires a synergistic effect with N element, if the ratio of the sum of the contents of V and Ti elements to the content of N element is lower than 6.5, the N content required for precipitation is exceeded, the gas content in the steel increases, and toughness is impaired, so the lower limit of (V+Ti) / N is set to 6.5. If the ratio is higher than 10.5, the precipitation amount of Ti and V elements is a low proportion of their total content, and the precipitation strengthening effect is insufficient, so the upper limit of (V+Ti) / N is set to 10.5.
[0041] According to the standard GB / T 1591, carbon equivalent (CEV) is a calculated value based on the above element content, and is also a standard index for evaluating weldability. In order to effectively exert the effect of each chemical component, CEV should be 0.30% or more, with the lower limit set at 0.30%. As CEV increases, when used in welding, both the amount of preparatory work before welding and the cold cracking susceptibility after welding increase, so in order to facilitate subsequent welding of the product, the upper limit is set at 0.48%.
[0042] Phosphorus (P): An impurity element that is prone to solidification segregation and concentration, impairs plasticity and toughness, and has a negative effect on weldability. The upper limit is set at 0.015%. Sulfur (S): An impurity element that forms long inclusions during rolling, which disrupt the atomic arrangement at the contact surface, making the material highly energetic and prone to cracking, and impairing toughness and through-thickness performance. The upper limit is set at 0.005%.
[0043] Oxygen (O): An impurity element that forms oxide inclusions with multiple other elements, forms brittle fracture bases, and impairs plasticity, toughness, and through-thickness performance. The upper limit is set at 0.0060%.
[0044] The extra-thick gauge hot-rolled H-beam according to the present invention is sampled at 1 / 6 width and 1 / 4 thickness from the flange end for mechanical property evaluation in accordance with the GB / T 2975 standard, and the microstructure is also characterized at this location. The microstructure contains 85% to 98% acicular ferrite by area, the remaining structure being bainite or retained austenite, with the bainite content being 2% or less, where the width dimension of the ferrite grains is 40 μm or less, but the difference in the acicular ferrite content in different regions along the flange thickness direction is 16% or less.
[0045] More preferably, the microstructure contains, by area percentage, 85% to 91% acicular ferrite at a location 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange, with the remainder of the structure being bainite and retained austenite, with the bainite content being 2% or less, where the width dimension of the ferrite grains is 20 μm or less, and the difference in the acicular ferrite content in different regions along the thickness of the flange is 9% or less.
[0046] More preferably, the microstructure contains, in area percentage, 91% to 98% acicular ferrite on the flange surface at a position 1 / 6 the width and 1 / 4 the thickness from the end of the flange, the remaining structure being bainite and retained austenite, with the bainite content being 1% or less, wherein the width dimension of the ferrite crystal grains is 20 μm to 40 μm, and the difference in the acicular ferrite content in different regions along the thickness direction of the flange is 9% to 16%.
[0047] Since the long axis direction of acicular ferrite is not constant, an interlocking structure is formed at the grain boundaries, and the distribution in the thickness direction of the flange is similar. In terms of improving plasticity, toughness, and performance in the thickness direction of the flange, acicular ferrite is clearly superior to bainite and pearlite, and its strength-enhancing effect is also greater than that of pearlite, making it an important structure for improving the overall mechanical properties of the product.
[0048] If the content of acicular ferrite is lower than 85% at the position of 1 / 6 width and 1 / 4 thickness from the end of the flange, the total content of acicular ferrite within the entire thickness will be insufficient, and pearlite may even be generated, so the beneficial effect of acicular ferrite cannot be fully exerted, and the plasticity, toughness and performance in the thickness direction will be impaired, so the lower limit of the content is set to 85%. When acicular ferrite precipitates, C element will inevitably be concentrated in other regions and form bainite or residual austenite during cooling after rolling, and cannot be completely transformed into acicular ferrite, so the upper limit of the content is set to 98%.
[0049] Since the distribution of precipitated bainite is relatively concentrated, the continuity of the matrix is destroyed, and if the content exceeds 2%, the plasticity and toughness are impaired. Therefore, the upper limit of the content is set at 2%.
[0050] The acicular ferrite grains are strip-shaped and have a long axis ratio of usually 2:1 to 5:1. It is feasible to limit the width of the grains. Reducing the grain size can improve the strength, plasticity and toughness, and improve the uniformity of the grain size in the thickness direction, which is helpful in improving the performance in the thickness direction. If the width is greater than 40 μm, the overall mechanical properties will be reduced. Therefore, the upper limit of the width is set to 40 μm.
[0051] If the difference in the content of acicular ferrite in the thickness direction of the flange exceeds 16%, the difference in plasticity in different regions will increase, and when subjected to tensile action along the thickness direction, different regions will not be able to deform in a coordinated manner, and the stress difference on both sides of the interface will exceed the crack nucleation energy, which is likely to cause cracks to form and the performance along the thickness direction will be impaired. Therefore, the difference in the content of acicular ferrite in different regions along the thickness direction of the flange should be no more than 16%.
[0052] The method for producing hot-rolled H-beam of extra-thickness standard according to the present invention mainly comprises the following production steps: pretreatment of molten iron → converter smelting → argon gas injection, refining in an LF furnace → blank heating → blooming rolling → rolling in a universal mill (rapid cooling before rolling begins) → staged cooling after rolling (rapid cooling + air cooling).
[0053] In the method for producing hot-rolled H-section steel of extra-thickness standard according to the present invention, a beam blank is used for rolling, the heating temperature of the blank is controlled to 1200° C. to 1350° C., and the heating time is set to 120 minutes or more.
[0054] More selectively, the heating temperature is 1200° C. to 1260° C., and the heating time is 122 min to 144 min.
[0055] More selectively, the heating temperature is 1260° C. to 1350° C., and the heating time is 168 min to 173 min.
[0056] The purpose of blank heating is to dissolve the alloy components, to make the structure uniform, and to reduce the rolling deformation resistance.
[0057] If the temperature is lower than 1200°C, the alloy elements cannot be fully dissolved, and the precipitates containing Ti and Nb elements form particles with non-uniform sizes during precipitation, and cannot be diffused and distributed, so the pinning and strengthening effects cannot be achieved, so the lower limit is set to 1200°C.If the temperature exceeds 1350°C, the size of the original crystal grains increases, which is unfavorable to the diffusion and distribution of the precipitates, and cracks are easily formed on the surface and superficial layer due to excessive sintering, so the upper limit is set to 1350°C.
[0058] If the heating time is less than 120 min, the blank cannot be sintered to its core, and the alloy elements cannot be sufficiently dissolved and homogenized, so the lower limit is set to 120 min. From the viewpoint of production economy, such as reducing oxidation burnout and reducing heating energy consumption, it is better not to exceed 180 min.
[0059] In the method for producing hot-rolled H-beam of extra-thickness according to the present invention, the surface temperature of the flanges reaches 1000° C. or higher after blooming is completed.
[0060] More preferably, the surface temperature of the flange is greater than or equal to 1020°C.
[0061] More preferably, the surface temperature of the flange is greater than or equal to 1050°C.
[0062] The purpose of blooming is to shape the blank and provide a suitable blank shape for rolling by universal mill. After blooming is completed, the purpose of controlling the surface temperature of the flange is to form a certain temperature gradient from the surface to the core through fast cooling, and enhance the deformation penetration in the rolling stage by universal mill. After blooming is completed, the temperature of the core of the flange is higher than the surface temperature. When the surface temperature is less than 1000℃, the core temperature is less than 1100℃. When the flange surface is cooled quickly in the rolling stage by universal mill, the overall heat capacity is small, the temperature drop of the core is fast, and an effective temperature gradient cannot be formed from the surface to the core, which affects the deformation penetration effect. Therefore, the lower limit is set to 1100℃.
[0063] In the method for producing hot-rolled H-beam of extra-thickness standard according to the present invention, before rolling using a universal mill, the flange surface is cooled to 700°C to 800°C by fountain cooling at a cooling rate of 20°C / s or more, and then the steel is placed in the universal mill for rolling.
[0064] Further optionally, before rolling by the universal mill, the flange surface is cooled to 740°C to 800°C by fountain cooling at a cooling rate of 22°C / s or more, and then put into the universal mill for rolling.
[0065] Further optionally, before rolling by the universal mill, the flange surface is cooled to 700°C to 740°C by fountain cooling at a cooling rate of 32°C / s or more, and then put into the universal mill for rolling.
[0066] The purpose of rolling with a universal mill is to compressively deform the flanges and web plate in the thickness direction to obtain the shape and dimensions of the finished product.
[0067] The purpose of the fast cooling before rolling by universal mill is to form a certain temperature gradient from the surface to the core in the thickness direction of the flange, during rolling, the surface temperature is low and the deformation resistance is large, and with rolling, the compression deformation continues to progress, and the deformation gradually penetrates to the core where the temperature is higher and the deformation resistance is small. Practice shows that with the increase of the temperature gradient, the deformation penetration effect is enhanced, the strain accumulation in the core increases, and the difference in strain accumulation from the surface to the core decreases accordingly. By increasing the strain accumulation, the nucleation position is increased, the driving force is increased, and the precipitation of acicular ferrite is promoted and refined. Reducing the difference in strain accumulation in the thickness direction of the flange is conducive to reducing the difference in the content of the structure in different regions in the thickness direction and improving the uniformity of the structure.
[0068] Since it is difficult to quickly measure the temperature of the core of the flange during production, the surface temperature, which is easier to measure, is used as the process parameter.
[0069] If the cooling rate is less than 20° C. / s, the cooling rate of the surface is too slow, and the heat from the core cannot be conducted to the surface layer in a sufficient time to obtain an effective temperature gradient.
[0070] If the cooling temperature of the flange surface is cooled below 700°C, the core temperature is low, the deformation resistance of this area is large, affecting the deformation penetration effect, and the energy consumption is too large, so the lower limit is set to 700°C. If the temperature is higher than 800°C, the work hardening degree of the surface is insufficient, and the deformation is still concentrated on the surface, affecting the deformation penetration effect, so the upper limit is set to 800°C.
[0071] In the method for producing hot-rolled H-beam of extra-thickness standard according to the present invention, after the rolling by the universal mill is completed, the flange surface of the rolled material is cooled to 480°C to 530°C by fountain cooling at a cooling rate of 5°C / s to 13°C / s, and then air-cooled. In this case, a low-temperature furnace may generally be used.
[0072] Further optionally, after the rolling by the universal mill is completed, the flange surface is cooled to 505°C to 530°C by fountain cooling at a cooling rate of 5°C / s to 9°C / s, and then air-cooled.
[0073] Further optionally, after the rolling by the universal mill is completed, the flange surface is cooled to 480°C to 505°C by fountain cooling at a cooling rate of 9°C / s to 13°C / s, and then air-cooled.
[0074] The purpose of rapid cooling after rolling with a universal mill is to suppress the precipitation of blocky ferrite and pearlite, avoid the precipitation of bainite, and promote the formation of fine acicular ferrite as much as possible. The temperature range of ferrite pre-eutectoid and pearlite precipitation is passed at high speed, the cooling rate is higher than the critical cooling rate of both and an upper limit is set, the flange surface is fountain cooled, and sufficient cooling time is given to the core for heat conduction. During final cooling, the temperature range of the entire flange thickness is controlled to 480℃ to 580℃, and fine acicular ferrite is sufficiently precipitated during the air cooling stage.
[0075] If the cooling rate of the flange surface is lower than 5℃ / s, the cooling rate of the core will decrease, and massive ferrite or pearlite distributed in stripes will precipitate, impairing toughness and plasticity, so the lower limit is set to 5℃ / s. If the cooling rate is higher than 13℃ / s, the total cooling time will be insufficient, the heat conduction of the core will be insufficient, the air-cooling start temperature will be high, and a lot of pearlite will be formed, impairing toughness and plasticity, so the upper limit is set to 13℃ / s.
[0076] If the cooling temperature of the flange surface is lower than 480°C, the surface and nearby regions will enter the upper bainite precipitation zone, more than 3% bainite will be formed, acicular ferrite will be formed in the core region, the structure difference will be large, and the through-thickness performance will be impaired, so the lower limit is set to 480°C. If the cooling temperature is higher than 580°C, the air-cooling start temperature of the core will increase, and a lot of blocky ferrite will be formed and precipitated, and wide acicular ferrite will be formed on the surface and nearby regions, which will impair the toughness and through-thickness performance, so the upper limit is set to 580°C.
[0077] In the extra thick hot rolled H-section steel according to the present invention, the flange thickness ranges from 90 mm to 150 mm, and the web plate thickness ranges from 50 mm to 120 mm.
[0078] More preferably, the flange has a thickness range of 90 mm to 115 mm.
[0079] More preferably, the flange has a thickness range of 115 mm to 150 mm.
[0080] Due to the design of heavy-duty supporting structural members requiring a certain strength and rigidity, the thickness of the flange of the hot-rolled H-shaped steel used must be at least 90mm, with the lower limit being 90mm. If the thickness exceeds 150mm, a larger beam blank is required, which requires large equipment investment and high production difficulty, and the flange is too thick, limiting the rolling deformation penetration and controlled cooling penetration, so the upper limit is set to 150mm.
[0081] According to the relevant requirements of structural design and the technical characteristics of hot-rolled H-section steel, when the flange thickness is within the range of 90mm~150mm, from the standpoint of structural stability and production feasibility, the thickness of the web plate should be 50mm~120mm.
[0082] The following Tables 1 to 4 show the chemical compositions, production process parameters, microstructures, and mechanical properties of Examples 1 to 10 provided by the present invention, respectively.
[0083] [Table 1]
[0084] [Table 2] Note: The temperatures and cooling rates during blooming and universal mill rolling are for the flange surface.
[0085] [Table 3]
[0086] In the extra-thickness hot-rolled H-section steel of the present invention, samples are taken at 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange in accordance with the provisions of standard GB / T 2975. The tensile yield strength measured at room temperature should be 460 MPa or more, the tensile strength measured at 540 MPa or more, and the breaking elongation measured at 24.0% or more in accordance with standard GB / T 228.1. The impact energy measured at -20°C should be 80 J or more in accordance with standard GB / T 229. The through-thickness performance measured in accordance with standard GB / T 5313 should reach the Z35 level.
[0087] [Table 4]
[0088] As can be seen from the examples provided in Tables 1 to 4, when the method described in the present invention is used to produce hot-rolled H-section steel with an extra-thickness specification of a flange thickness of 90 mm to 150 mm, the yield strength at room temperature reaches 464 MPa to 522 MPa, the tensile strength is 597 MPa to 649 MPa, the elongation at break is 24.0% to 32.0%, the impact energy at -20°C is 84 J to 126 J, and the through-thickness performance exceeds the requirements of the Z35 level.
[0089] The above are merely preferred embodiments of the present invention, and the scope of protection of the present invention is not limited thereto, and any changes or replacements that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention shall be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the scope of protection defined in the claims.
[0090] All the points not described in detail in the present invention are techniques known to those skilled in the art.
Claims
1. The chemical components, in mass percentage, are: C: 0.04-0.11, Si: 0.10-0.40, Mn: 0.40-1.00, Cr: 0.40-1.00, Cu: 0.10-0.40, Nb: 0.020-0.060, V: 0.040-0.100, Ti: 0.010-0.025, Al: 0.010-0.030, N: 0.0060-0.0120, P: ≦0.015, S: ≦0.
005. , O:≦0.0060, 0.090%≦Nb+V+Ti≦0.170% and 6.5≦(V+Ti) / N≦10.5 are satisfied, with the balance being Fe and trace amounts of residual elements, and the calculation is performed according to CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15, and the chemical composition satisfies 0.30%≦CEV≦0.48%, The H-shaped steel has a flange thickness of 90 mm to 150 mm, The hot-rolled H-shaped steel of extra-thickness standard has a microstructure containing, in terms of area percentage, 85% to 98% acicular ferrite at a position 1 / 6 / width and 1 / 4 / thickness from an end of a flange of the H-shaped steel, with the remaining structure being bainite or retained austenite, the bainite content being 2% or less, the width dimension of a ferrite crystal grain being 40 μm or less, and the difference in the acicular ferrite content in different regions along the thickness direction of the flange being 16% or less.
2. The chemical components are, in mass percentage, C: 0.04-0.07, Si: 0.10-0.30, Mn: 0.80-1.00, Cr: 0.40-0.90, Cu: 0.10-0.25, Nb: 0.040-0.060, V: 0.040-0.080, Ti: 0.010-0.015, Al: 0.010-0.020, N: 0.0060-0.0100, P: ≦0.015, S: ≦0.005, 2. The hot-rolled H-section steel according to claim 1, wherein the chemical composition satisfies 0.30%≦CEV≦0.43%, the formula CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15 is used, and the formula CEV is calculated according to: C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15.
3. The chemical components, in mass percentage, are: C: 0.07-0.11, Si: 0.30-0.40, Mn: 0.40-0.80, Cr: 0.90-1.00, Cu: 0.25-0.40, Nb: 0.020-0.040, V: 0.080-0.100, Ti: 0.015-0.025, Al: 0.020-0.030, N: 0.0100-0.0120, P: ≦0.015, S: ≦0.005, O 2. The hot-rolled H-section steel according to claim 1, wherein the chemical composition satisfies 0.40%≦CEV≦0.48%, the Nb+V+Ti ratio is 0.130%<Nb+V+Ti≦0.170%, 8.5≦(V+Ti) / N≦10.5, and the balance is Fe and trace amounts of residual elements, and the calculation is performed according to CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15.
4. 4. The hot-rolled H-beam steel of extra-thickness standard according to claim 1, characterized in that at a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange of the H-beam, the microstructure contains, in terms of area percentage, 85% to 91% acicular ferrite, the remaining structure is bainite or retained austenite, the bainite content is 2% or less, the width dimension of the ferrite crystal grains is 20 μm or less, and the difference in the acicular ferrite content in different regions along the thickness direction of the flange is 9% or less.
5. 4. The hot-rolled H-beam steel of extra-thickness standard according to claim 1, characterized in that at a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange of the H-beam, the microstructure contains, in terms of area percentage, 91% to 98% acicular ferrite, the remaining structure is bainite or retained austenite, the bainite content is 1% or less, the width dimension of the ferrite crystal grains is 20 μm to 40 μm, and the difference in the acicular ferrite content in different regions along the thickness direction of the flange is 9% to 16%.
6. The hot-rolled H-shaped steel according to any one of claims 1 to 3, characterized in that, at a position 1 / 6 of the width and 1 / 4 of the thickness from the end of the flange of the H-shaped steel, the tensile yield strength at room temperature is 460 MPa or more, the tensile strength is 540 MPa or more, the breaking elongation is 24.0% or more, the impact energy value at -20°C is 80 J or more, and the performance in the thickness direction reaches a Z35 level.
7. Heating the blank under conditions of a heating temperature of 1200° C. to 1350° C. and a heating time of 120 min to 180 min; performing blooming and, after the rolling is completed, a surface temperature of the flange is 1000° C. or more; 7. A method for producing hot-rolled H-beam of extra-thickness standard according to claim 1, further comprising the steps of: fountain cooling at a cooling rate of 20°C / s or more so as to rapidly cool the flange surfaces to 700°C to 800°C; subsequently, placing the material in a universal mill for rolling; and after completing rolling with the universal mill, first rapidly cooling the flange surfaces of the rolled material to 480°C to 530°C at a cooling rate of 5°C / s to 13°C / s by fountain cooling, and then air cooling.
8. A method for producing hot-rolled H-section steel of extra-thick standard as described in claim 7, characterized in that a beam blank is used as the blank, the beam blank is subjected to blooming, and after rolling is completed, the surface temperature of the flange is 1020°C or higher.
Citation Information
Patent Citations
Steel for building structure and production method therefor
JP2002294391A
THERMO-MECHANICAL CONTROL PROCESS TYPE 590 MPa-CLASS H-SHAPE STEEL, AND ITS MANUFACTURING METHOD
JP2006322019A
High-strength ultra-thick h shape steel and process for production thereof
WO2011065479A1
H-shaped steel and process for producing same
WO2014080818A1
H-shaped steel and method for producing same
WO2018169020A1
